Logística reversa das embalagens de agrotóxicos no campo sergipano - Santiago, Josilda Almeida Correia (2023)
Brazil stands out on the world stage as a large consumer of pesticides. This practice has been widespread since the post-war period, when the agricultural model propagated by the Green Revolution received support from the Brazilian government, in addition to financial investment. The chemical agrarian model established in the country has been responsible for serious changes in socio-environmental dynamics. Given this reality, the problem of this research is related to the irregular disposal of pesticide packaging, as they constitute a source of environmental pollution when they are not properly disposed of, potentially contaminating the soil, underground water reservoirs and the air with the release of gases. toxic substances arising from pesticide residues contained in packaging. The central objective is to describe the reverse logistics process for pesticide packaging and the challenges related to its adequate implementation, analyzing how it works in different application sectors. The dialectical method was chosen to support the methodological path, as it was understood that the impasse generated by the use of pesticides deserves a reflection that contemplates reality in its entirety, considering political, social, economic and cultural aspects. This is a basic research, with a qualitativequantitative approach, of a descriptive and exploratory nature because it used a bibliographic and documentary survey to collect data regarding the disposal of pesticide packaging in Brazil, especially in the Sergipe countryside, examining the legislation that regulates the use of agrochemicals in Brazil, as well as the final destination of postconsumer packaging. In order to explore the context in which the problem of this research is inserted, an analysis of agricultural practice was carried out, discussing the existing correlation between food production and the use of pesticides, in addition to addressing the impacts of the traditional agrarian model on the environment and human health, as well as market influences on public agents that regulate the use of pesticides in Brazil. The Reverse Logistics System for pesticide packaging developed by INPEV was explored, analyzing its organization and the data presented regarding the quantity of packaging removed from the Brazilian countryside. Such data were compared with the results of research carried out in Brazil that dealt with the disposal of pesticide packaging. It was found that despite the Campo Limpo System being relevant to the operation of reverse logistics in Brazil, small municipalities do not comply with what the legislation determines. In Sergipe, ARDASE is highly relevant to complying with legislation regarding the proper disposal of pesticide packaging, and in partnership with some city halls promotes the itinerant collection of these packaging and sends them to recycling or incineration plants. As a product, a children's educational book presented as an ebook was created, which tells the story of two girls who love spending their holidays at their grandmother's farm and in contact with nature. The story evolves gradually, emphasizing the main characters' ability to observe and their innate curiosity, until the moment they find themselves faced with a great mystery that needs an explanation.